Instagram and Achilles tendon surgery: Evaluation of patients' perceptions of surgery: Instagram and Achilles tendon surgery - Kultur, Yigit; Bal, Emre; Tutuncu, Mehmed Nuri; Gasimov, Elviz; Biscevic, Mirza; Tezer, Mehmet (Journal of Surgery and Medicine, 2024)
Background/Aim: The primary objective of this study was to conduct comprehensive research and analysis of patient-generated content related to Achilles tendon surgery on the social media platform Instagram. The aim was to gain deeper insights into patients' experiences during the perioperative period, which may contain valuable information pertinent to their condition, information of which the physicians may be unaware. Methods: A search was conducted on the Instagram database, covering a period of 78 months from February 2015 to August 2021. Posts utilizing the hashtags "#achillessurgery" and "#achillesrepair" were included in the analysis. Posts were assessed using a binary scoring system, considering variables such as tone, media format, return to work, rehabilitation or physical therapy, return to sports, images related to the ankle (e.g., scars, stitches, casts, dressings, walking boots), activities of daily living, and pain. Results: A total of 500 posts were reviewed, and a positive tone was observed in 77.8% of these. The average Instagram like ratio for these posts was computed as 9%. Statistical analysis revealed a significant relationship between post content and tone status (P=0.001). Specifically, within the positive tone group, informative content about the disease was comparatively lower and statistically significant when compared to exercise training and patient experience (P=0.001). Additionally, exercise training posts were found to be significantly lower than patient experience posts (P=0.001) within the positive tone group. In contrast, within the negative tone group, patient experience posts were significantly higher compared to informative content and exercise training posts (P=0.001). Moreover, the quantity of informative posts markedly surpassed the number of posts related to exercise training (P=0.001). Conclusion: In the positive tone category, people tended to emphasize personal experiences and participate in posts related to exercise training rather than actively seeking or exchanging information about the disorder. On the other hand, within the negative tone group, individuals were more likely to share adverse experiences, pursue support, and seek a deeper understanding from others. Their priority may also lie in sharing and gaining information specifically about the disorder. Our exploration of the use of social media platforms to delve into patient perspectives on Achilles tendon surgery provides an alternative insight into patients' experiences with the surgical process. By comprehending the content shared by patients on social media, surgeons may gain an improved opportunity to assess and address the surgical experience of their patients more effectively, ultimately contributing to enhanced patient care.